Produção de concreto autoadensável com uso de fíler calcário de resíduo de serragem de Pedra Cariri - Mercês , Uiliana Márcia da Silva (2017)
The use of waste from Dimension Stone Industry as an inert material can be a good way to promote the sustainability of the construction sector. The Cariri stone is one of the dimension stones explored in state of Ceara, in Brazil. Thus, this work was developed with the main goal of studying a self-compacting concrete production (SCC) using Cariri stone sawdust waste (CSSW) in partial replacement with the natural fine aggregate. The SCC was designed using the method proposed by Melo (2005) considering two w/c ratios (0.57-0.70), and 10% of CSSW. The study was carried out in three stages: material characterization, mortar phase evaluation and SCC phase evaluation. In the fresh state, SCC was evaluated for fluidity, plastic viscosity, blocking capacity and segregation resistance, using V funnel, J-Ring, L-box and segregation column. In the hardened state, the SCC was evaluated for axial compressive strength, splitting tensile strength and water absorption, void index and specific density. The results showed that CSSW improve SCC cohesiveness and homogeneity, and it is feasible to apply up to 10% of CSSW in SCC production.